A Corpus-Based Critical Discourse Analysis of English Discourse in The Jakarta Post - Nur Nabilah Fauziyah; Ni Gusti Ayu Roselani (k@ta: A Biannual Publication on the Study of Languange and Literature, 2025)
This study examines English discourse construction in an Indonesia's English-language newspapers, The Jakarta Post. The researchers analyzed data over a 15-year period (from January 1, 2009, to December 31, 2023), focusing on the core terms of English education and multilingualism. A corpus was created to analyze 79 articles containing 55,047 words, using AntConc (version 4.2.3). The study employed Fairclough's (2003) textual analysis, Pennycook's (2000) classification of English global position, and Holborow's (2012) neoliberalism as theoretical frameworks to categorize language ideologies. The researchers also conducted Foucauldian Discourse Analysis, as explained by Walshaw (2007), to explore power/knowledge. The findings reveal multiple ideologies fashioned by The Jakarta Post's authors, including colonial celebration, language ecology, linguistic imperialism, language rights, and neoliberalism. The results suggest The Jakarta Post has constructed contradictory ideologies. While the articles have grown increasingly concerned about biased language views, they still perpetuate English mainstream discourses. This may be attributed to English hegemony and neoliberalism in various contexts.